Dehiscence of a pulmonary bioprosthesis with a focal dissection of the pulmonary artery in a patient with congenital pulmonic stenosis. Issue 5 (27th March 2017) - Yucel, Evin; Bhatt, Ami; Mihos, Christos G.; Ghoshhajra, Brian B.; DeFaria Yeh, Doreen
Abstract : Pulmonary valve replacement (PVR) is the most common adult congenital cardiac operation performed. Valve degeneration leading to prosthetic stenosis and/or regurgitation is a long‐term risk in this population and may be associated with paravalvular leak (PVL). Complications involving the proximal pulmonary artery, including dissection, are less clearly defined. Herein, we report the case of a 30‐year‐old patient with a history of multiple pulmonary valve interventions secondary to congenital pulmonic stenosis, who developed dehiscence of a bioprosthetic PVR associated with significant paravalvular leak (PVL) and further complicated by a focal dissection of the proximal pulmonary artery.